Evaluasi kesesuaian penulisan resep pada kasus ISPA non pneumonia di poli MTBS Puskesmas Kecamatan Cengkareng, Jakarta - Sauriasari, Rani; Aulia, Annisa Azka Hikmawati; Swastika, Adisa (UI Scholars Hub, 2018)
Acute respiratory infections (ARI) is one of the major health problems in Indonesia. There are three classifications of cases of ARI, consist of pneumonia, severe pneumonia and non pneumonia. This study aimed to find an overview of the use of antibiotics and the evaluation of suitability prescriptions performed in cases of non pneumonia Acute Respiratory Infections (ARI) in IMCI Polyclinic, Cengkareng District Community Health Centre (Puskesmas Cengkareng), West Jakarta. Evaluation for the prescription suitability was useful to find the percentage of the suitability of prescribing on the existing management. This activity was done using retrospective method with data of 100 children patients suffered from non pneumonia cough obtained from registration book on IMCI Polyclinic during February 2016. The existing data was then matched to the patient status and prescription books that went into the dispensary unit at second floor. Furthermore, we evaluated the suitability of the reference book titled Integrated Management Scheme for Toddler Patients/Bagan Manajemen Terpadu Balita Sakit (MTBS), issued by the Ministry of Health of the Republic of Indonesia in 2011. The results showed that the percentage of antibiotic used in the sample was 59.6%, which the most frequent antibiotic used was amoxicillin. Therefore we concluded that the prescription compliance with IMCI guidelines in Puskesmas Cengkareng at February 2016 was inadequate yet.